Water-soluble Vitamins in the Prophylaxis and Treatment of Metabolic Diseases and Related Disorders - Agostini, Stefano (British Journal of Healthcare and Medical Research, 2024)
This article aims to define the complex relationships between cellular biochemistry, metabolic diseases, and the effects of some drugs. Water-soluble vitamins (WSVs) are indispensable cofactors in the reactions of the Krebs cycle, folate cycles, methionine cycles, numerous biochemical reactions related to these cycles, and the electron transport chain. The function of each vitamin is carried out in concert with the functions of others in a complex network of biochemical reactions that require the presence of all WSVs simultaneously to maintain cellular homeostasis. The chemical reactions in which WSVs are involved occur mainly, but not exclusively, in the mitochondria and are essential for cellular catabolism and anabolism. Restricting the availability of just one of them hampers the functions of all others, contributes to mitochondrial dysfunction and hinders cellular metabolism. This should be a fundamental consideration in assessing the action of these vitamins and their potential therapeutic use. Deficiencies, whether severe, marginal, functional, or increased demand for WSVs, are widespread in populations of developed countries, despite seemingly well-nourished populations. Obesogenic diets provide an excess of energy substrates associated with inadequate intake of WSVs. This contributes to mitochondrial dysfunction and represents a contributing factor in the development of metabolic diseases and related disorders. The treatment of metabolic diseases includes the administration of drugs that can induce depletion of WSVs. Some drugs used in the treatment of patients suffering from metabolic diseases increase the risk of type 2 diabetes mellitus and peripheral neuropathies, disorders associated with WSVs deficiency. Based on these premises, this article highlights the importance of proper cellular biochemical balance and the use of WSVs as an inseparable unit for the prophylaxis and treatment of metabolic diseases, even in relation to the drugs commonly used.